Association between expression level of the miR-320, miR-182, miR-223 and miR-486 and body composition among young Polish female volleyball players - Pruszkowska, Paulina; Cichy, Ireneusz; Ignasiak, Zofia; Kochan, Katarzyna; Kociuba, Marek; Kozieł, Sławomir; Sebastjan, Anna; Ściślak, Marcin; Żądzińska, Elżbieta; Rokita, Andrzej (Anthropological Review, 2024)
The expression of circulating microRNAs appears to be a promising indicator of physical strength. The objective of this study was to determine whether there is an association between the expression level of four selected microRNAs and body composition over time among young female volleyball players. Blood samples and body composition measurements were taken from 7 females who are Polish volleyball players before and after 5 matches played out between the years 2017 and 2018. The blood spots were used to assess the expression of four microRNAs: miR-320, miR-182, miR-223, and miR-486. Fat mass, PFB% and BMI were positively correlated with expression level (exp.l) of miR-182. The miR-320 the exp.l was positively correlated with muscle mass and TBW. There were inverse correlations between miR-486 exp.l and PBF%, as well as between miR-486 exp.l and body mass, muscle mass, TBW, FFM, and BMR. Conversely, there were positive correlations between miR-486 exp.l and body mass and fat mass. The miR-182 may be positively correlated with fat tissue, miR-320 was positively correlated with muscle mass, and miR-486 was negatively correlated with fat mass. Overall, our study shows that the expression of miR-182, miR-320, and miR-486 is associated with body composition. The results of our study also suggest that exercise may decrease the level of miR-486. The authors are grateful for the support of the Laboratory of Microscopic Imaging and Specialized Biological Techniques of the University of Lodz.